2017
DOI: 10.1007/s10461-017-1747-0
|View full text |Cite
|
Sign up to set email alerts
|

In Australia, Most HIV Infections Among Gay and Bisexual Men are Attributable to Sex with ‘New’ Partners

Abstract: It has been estimated that the majority of global HIV infections among gay and bisexual men (GBM) can be attributed to sex within a committed relationship. In Australia, however, negotiated safety, whereby HIV-negative regular partners agree to discard condoms with each other but commit to consistent condom use with other partners, has been promoted as a key component of the HIV prevention response. We asked GBM recently diagnosed with HIV to describe their relationship to the person they believed to be the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…3 Approximately one-third of infections among newly diagnosed men in Australia are estimated to be from regular partners, [4][5][6] whereas modelling from the US estimates that 68% of infections in GBM are from 'main' partners. 7 Intimacy and familiarity with partners have been associated with increased CLAI among GBM, [8][9][10][11] and HIV prevention and research have described ongoing sexual relationships as potentially high risk for HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Approximately one-third of infections among newly diagnosed men in Australia are estimated to be from regular partners, [4][5][6] whereas modelling from the US estimates that 68% of infections in GBM are from 'main' partners. 7 Intimacy and familiarity with partners have been associated with increased CLAI among GBM, [8][9][10][11] and HIV prevention and research have described ongoing sexual relationships as potentially high risk for HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…'fuckbuddies') are common among GBM. 12,15,16 In Australia, among newly HIV-diagnosed GBM who ascribed their HIV infection to a regular partner, over two-thirds considered them to be 'fuckbuddies' rather than 'boyfriends' 6,17 and, among these newly diagnosed GBM, the majority of transmissions from regular partners were believed to have occurred within the first 3 months of meeting. Similarly, research on serodiscordant GBM regular partnerships, where one partner is HIV-positive and the other is HIVnegative, demonstrated that the HIV transmission rate was approximately 6 per 100 person-years in the first year, but decreased to approximately 1 per 100 person-years thereafter.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations